EVERYDAY MEMORY AND METAMEMORY IN INSTITUTIONALIZED OLD SUBJECTS - Pérez, Miguel; Pelegrina, Santiago; Justicia Justicia, Fernando; Godoy, Juan F. (Anales de Psicología / Annals of Psychology)
The main purpose of this study was to examine both the performance in memory tasks such as the perceptions that old people have of its memory (metamemory), as well as the possible relationship (that may exist) between them. As an objetive measure of everyday memory, a list of selected tasks was used. As a traditional measure of memory, the Rey Auditive-Verbal Learning Test (RAVLT) of Rey (1964) was used. Finally, the metamemory was evaluated through the Metamemory In Adulthood (MIA) of Dixon, Hultsh and Hertzog (1988). The results refering to everyday memory showed significant differences among young and old subjects in all the tests. Besides, the results in RAVLT showed significant differences between young and old subjects in the curve of learning, in the span of memory and in the effect produced in memory due to the delay and interference. As for the metamemory, significant differences appeared in young and old subjects in MIA related to achievement, change and task scales. Finally, each canonical correlation analysis was carried out in order to study the relationship between the RAVLT and everyday memory measures and between the MIA and everyday memory. A significant correlation appeared only in the first case. These results are discussed within the scope of the studies on cognitive deterioration in old subjects and the lack of relationship among objetive and subjetive measures of memory.